2011
DOI: 10.1016/j.abb.2011.02.013
|View full text |Cite
|
Sign up to set email alerts
|

The significance of regulatory light chain phosphorylation in cardiac physiology

Abstract: It has been over 35 years since the first identification of phosphorylation of myosin light chains in skeletal and cardiac muscle. Yet only in the past few years has the role of these phosphorylations in cardiac dynamics been more fully understood. Advances in this understanding have come about with further evidence on the control mechanisms regulating the level of phosphorylation by kinases and phosphatases. Moreover, studies clarifiying the role of light chain phosphorylation in short and long term control o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
104
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(108 citation statements)
references
References 61 publications
2
104
2
Order By: Relevance
“…This modification has been observed to bring the S1 heads of myosin closer to actin, enhancing the calcium sensitivity and duty ratio 136 . Myosin RLC phosphorylation is an important regulatory control in all types of muscle 137,138 ; it is the main mechanism controlling contraction in smooth muscle (which does not utilize a troponin complex). In cardiac muscle, β-adrenergic stimulation does increase RLC phosphorylation, but on a much slower timescale than is observed in skeletal or smooth muscle 137 .…”
Section: Myosin Regulatory Chain Phosphorylationmentioning
confidence: 99%
“…This modification has been observed to bring the S1 heads of myosin closer to actin, enhancing the calcium sensitivity and duty ratio 136 . Myosin RLC phosphorylation is an important regulatory control in all types of muscle 137,138 ; it is the main mechanism controlling contraction in smooth muscle (which does not utilize a troponin complex). In cardiac muscle, β-adrenergic stimulation does increase RLC phosphorylation, but on a much slower timescale than is observed in skeletal or smooth muscle 137 .…”
Section: Myosin Regulatory Chain Phosphorylationmentioning
confidence: 99%
“…cRLC is at the thick filament end of the myosin head, where it joins the coiled-coil tail that forms the thick filament backbone. cRLC is partially phosphorylated in vivo under basal conditions (8)(9)(10)(11)(12), and changes in its phosphorylation level are linked to heart disease (8,11,13,14). cRLC mutations associated with hypertrophic cardiomyopathy abolish cRLC phosphorylation in vitro (15), and mice expressing nonphosphorylatable cRLCs show severe cardiac dysfunction (10,16).…”
mentioning
confidence: 99%
“…Perry suggested that myosin light chains could exist as charged variants (Perrie et al 1972(Perrie et al , 1973, shortly after which phosphorylation was established as a significant mechanism in cardiac and skeletal muscle (Frearson and Perry 1975). Myosin RLC phosphorylationinduced enhancement of isometric force and increased rates of muscle contraction have been reported in a wealth of studies from different laboratories (Colson et al 2010;Davis et al 2001;Greenberg et al 2009;Scruggs and Solaro 2011;Sheikh et al 2012;Sweeney et al 1993;Warren et al 2012). Specifically, RLC phosphorylation was shown to accelerate the rate of cross-bridge entry into the force generating state by regulating the proximity as well as the interaction of myosin with actin, thereby increasing Ca 2+ sensitivity and amplitude of force at all activation levels (Colson et al 2010;Szczesna et al 2002).…”
Section: Genetic Mutations In Myosin Regulatory Light Chain Lead To Cmentioning
confidence: 99%
“…However, human ventricular RLC may only be singly phosphorylated (Ser-15) (Fig. 1) or singly deamidated (Asn-14 to Asp-14) (Scruggs et al 2010;Scruggs and Solaro 2011). These sites are mostly phosphorylated by a cardiac-specific MLCK (cMLCK), encoded by MYLK3, which, in addition to its role in Ca 2+ sensitization of myofilaments (Sweeney and Stull 1986), may serve as an adaptive mechanism to rapidly facilitate sarcomere organization in cardiac myocytes in response to hypertrophic stimuli associated with increased intracellular Ca 2+ (Aoki et al 2000).…”
Section: Introductionmentioning
confidence: 99%